2019
DOI: 10.1038/s42003-019-0615-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of spatacsin impairs cholesterol trafficking and calcium homeostasis

Abstract: Mutations in SPG11, leading to loss of spatacsin function, impair the formation of membrane tubules in lysosomes and cause lysosomal lipid accumulation. However, the full nature of lipids accumulating in lysosomes and the physiological consequences of such accumulation are unknown. Here we show that loss of spatacsin inhibits the formation of tubules on lysosomes and prevents the clearance of cholesterol from this subcellular compartment. Accumulation of cholesterol in lysosomes decreases cholesterol levels in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 58 publications
(89 reference statements)
3
38
0
Order By: Relevance
“…In mice, loss of Spg11 led to early cognitive and motor deficits, consistent with the symptoms observed in the majority of patients with mutations in the SPG11 gene (Branchu et al, 2017). Loss of spatacsin impairs the formation of membrane tubules in lysosomes and cause lysosomal lipid accumulation altering the homeostatic equilibrium between cholesterol trafficking and cytosolic calcium levels (Boutry et al, 2019b). Downregulation of spg11 in zebrafish resulted in abnormal axon outgrowth (Martin et al, 2012) and a range of developmental defects (Table 1) and CNS abnormalities.…”
Section: Spg11supporting
confidence: 60%
See 3 more Smart Citations
“…In mice, loss of Spg11 led to early cognitive and motor deficits, consistent with the symptoms observed in the majority of patients with mutations in the SPG11 gene (Branchu et al, 2017). Loss of spatacsin impairs the formation of membrane tubules in lysosomes and cause lysosomal lipid accumulation altering the homeostatic equilibrium between cholesterol trafficking and cytosolic calcium levels (Boutry et al, 2019b). Downregulation of spg11 in zebrafish resulted in abnormal axon outgrowth (Martin et al, 2012) and a range of developmental defects (Table 1) and CNS abnormalities.…”
Section: Spg11supporting
confidence: 60%
“…To date, it clearly emerged that HSP, HA, ASS, and other neurological disorders are part of a continuum of overlapping clinical conditions. For instance, the clinical overlap of HSP with HA or intellectual/ developmental disability is not new and so it is the overlap with the mechanisms involved in more common neurological conditions including amyotrophic lateral sclerosis, multiple sclerosis, Parkinson disease, and dementias (Patten et al, 2014;Parodi et al, 2017;Boutry et al, 2019b;Shribman et al, 2019). Since HSP and ASS are a group of disorders characterized by high genetic diversity, researchers have widely exploited the zebrafish as an in vivo model system of these pathologies.…”
Section: Conclusion and Future Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that the formation of tubules on lysosomes mediated by spatacsin allows the recycling of cholesterol from lysosomes. Loss of spatacsin led to an accumulation of cholesterol in lysosomes and decreased cholesterol content in plasma membrane (Boutry et al, 2019b), which could affect membrane properties and function. This highlights that impaired cholesterol trafficking and not only cholesterol overload in lysosomes could contribute to the pathology.…”
Section: Alteration Of Cholesterol Synthesis or Trafficking In Hspmentioning
confidence: 99%